Does Better Access to Finance Help Firms Deal with the COVID-19 Pandemic? Evidence from Firm-Level Survey Data - Amin, Mohammad (World Bank, Washington, DC, 2021)
The advent of the novel coronavirus (COVID-19) pandemic has led to a severe liquidity crunch among private firms. Yet, formal analysis of the impact of a liquidity crunch or access to finance on the performance of firms during the pandemic is limited. The present paper estimates the impact of access to finance in the period before the pandemic on the likelihood of a decline in sales of the firm during the pandemic. The results show a strong connection between the two. That is, firms with better access to finance are significantly less likely to experience a decline in sales, and this relationship is highly heterogenous. First, better access to finance reduces the likelihood of a decline in sales much more for firms that have a stronger long-standing relationship with important stakeholders such as skilled workers and input suppliers. These are firms that use more skilled relative to unskilled workers, firms in industries with a more complex network of input suppliers, and firms in countries where the cost of enforcing contracts with new input suppliers is high. Second, the impact of access to finance is less among firms that use more women relative to men workers. This is especially so in countries or societies that accord a higher value to women’s caregiving role than to their work outside the home. The paper argues that both of these heterogeneities are along expected lines and derive from the specific ways in which access to finance benefits firms in fighting the pandemic. Thus, they help to raise confidence against endogeneity concerns about the main results.